Impact of Pulse Oximetry Screening on the Detection of Duct Dependent Critical Congenital Heart Disease in Neonate - Mamun, Mohammad Abdullah Al; Hussain, Manzoor; Kar, Suntanu Kumar; Rima, Rezoana; Jabbar, Abdul (Bangladesh Journal of Child Health, 2017)
Background: Screening for congenital heart diseases (CHD) in newborn babies aid in early recognition, with the prospect of improved outcome. Currently there is no effective screening protocol for this condition. Pulse oximetry is highly specific for detection of critical CHD with moderate sensitivity that meets criteria for universal screening. Objective: To evaluate the use of pulse oximetry as a screening tool in early detection of critical CHD specially duct dependent critical CHD in asymptomatic newborn babies. Methodology: A cross sectional study conducted in Dhaka Shishu (Children) Hospital from October 2014 to June 2015. Newborns attended outpatient department or admitted in different wards with having gestational age >35 weeks and age between 24-48 hours were included and pulse oximetry screening was done. Oxygen saturation measurement <90%, or oxygen saturation measurements <95% in both extremities on three consecutive measurements separated by one hour, or a >3% absolute difference in oxygen saturation between the right hand & foot on three consecutive measurements was considered as pulse oximetry screening positive. Routine neonatal examination was done and clinical evidence of CHD was noted. Echocardiogram was done to rule out CHD. Data were analyzed by using SPSS and sensitivity, specificity and predictive values were calculated. Result: Total 510 neonate were screened during the data collection period. Mean age at screening was 34.99±8.4 hours, male were 322(63.1%) and female were 188(36.9%). Among the neonates 28(5.49%) were found pulse oximetry screening positive and 25(4.90%) were suspected as CHD by routine neonatal examination. Critical CHD were found in 21 cases out of 28 screening positive cases among them duct dependent critical CHD was found in 11 cases. Sensitivity of pulse oximetry to identify critical CHD was 77.77% and specificity was 98.55%. Sensitivity of pulse oximetry to identify duct dependent critical CHD was 78.57% and specificity 96.57%. Conclusion: Pulse oximetry is a good screening test for early identification of duct dependent critical CHD for those who have no obvious feature. So in resource poor country like Bangladesh if all neonatal health setup use pulse oximetry screening within 24-48 hours of life, it will increase early identification of duct dependent critical CHD. Bangladesh J Child Health 2016; VOL 40 (2) :85-91